2012
DOI: 10.1186/1755-7682-5-6
|View full text |Cite
|
Sign up to set email alerts
|

Thymic hyperplasia in a patient with Grave's disease

Abstract: Hyperplastic changes of the thymus may be found in patients with Graves' disease. However, this rarely presents as an anterior mediastinal mass, particularly among adults. In this report, we describe a 46-year old woman with Graves' disease and thymic hyperplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
2
5
0
Order By: Relevance
“…In addition to the 92 cases discussed by Deforges-Bullet et al [9], we found another 15 case reports of thymic enlargements associated with GD published to date [12][13][14][15][16][17][18][19][20][21][22]. Only 4 of these 107 cases in all were diagnosed as thymic malignancies (three thymomas and one T lymphoblastic lymphoma/leukemia [19][20][21]), while TH was confirmed in all the other cases.…”
Section: Review Of the Literaturesupporting
confidence: 42%
See 1 more Smart Citation
“…In addition to the 92 cases discussed by Deforges-Bullet et al [9], we found another 15 case reports of thymic enlargements associated with GD published to date [12][13][14][15][16][17][18][19][20][21][22]. Only 4 of these 107 cases in all were diagnosed as thymic malignancies (three thymomas and one T lymphoblastic lymphoma/leukemia [19][20][21]), while TH was confirmed in all the other cases.…”
Section: Review Of the Literaturesupporting
confidence: 42%
“…When TH is diagnosed in association with GD, in the absence of myasthenia gravis and/or suspect CT findings [16], it can generally be considered a benign condition, in which case only antithyroid treatment and radiological follow-up are warranted. The time to remission of TH under medical treatment varies considerably (from 2 to 24 months) and is impossible to predict before starting the therapy [35].…”
Section: Resultsmentioning
confidence: 99%
“…However, many hyperplasia cases presented with large soft tissue masses, which were easily detected on chest radiograph, were found misdiagnosed as thymoma. 9 -13 In patients with MG, Nicolaou et al 14 found thymic lymphoid hyperplasia can exhibit variable morphologies and sizes as it may appear normal (45% of cases), triangular-shaped diffusely enlargement with smooth margin (35%), or as a focal thymic mass (20%). This mass could not be differentiated with thymoma (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…These autoantibodies have a stimulating effect on the thyroid gland. The incidence of the disease in the population is 16 women and 3 men per 100 000 inhabitants / year [4].…”
Section: Discussionmentioning
confidence: 99%